PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, DAN PERCEIVED ENJOYMENT TERHADAP PENERIMAAN TEKNOLOGI INFORMASI (Studi Empiris di Kabupaten Sragen) - santosa, budi (Jurnal Studi Akuntansi Indonesia, 2012)
The purpose of this research is to examine the factors that influence the acceptance of IT by employee based on Technology Acceptance Model of (TAM). The model of this research adopts by Tangke (2004) using the perceived usefulness (PU), perceived ease of use (PEOU) and perceived enjoyment (PE) as an independent variable and Attitude (ATT) and the Acceptance of IT as a dependent variable. Data are collected using survey method and deliver directly to respondents. From the 112 distributed questionnaires, all qualified for further analysis. The data analyze by SEM. The results show that the factor directly affect to the acceptance of IT is perceived usefulness (PU) that defined as user perception concerning usefulness of IT and indirectly influenced by perceived ease of use (PEOU) factor and perceived enjoyment (PE) that defined as user perception concerning amenity and comfort in using technologi Information system. In addition, the perceived ease of use (PEOU) variable proved to have a significant influence toward the perceived usefulness (PU) variable.